Visible-Light-Mediated Energy Transfer Enables Intramolecular Cyclization of O‑Acetyloximes to Phenanthridines - Liu, Zi-Xuan; Yang, Xiu-Long; Li, Hao-Yuan; Du, Jian-Long; Niu, Xiaoying (Synlett, 2025)
O‑Acetyloximes underwent N–O bond cleavage/intramolecular cyclization under visible-light-mediated energy transfer to give phenanthridines. In contrast to the well-established approaches, no external oxidant, reductant, or additive is required for this reaction.
Keywords: energy-transfer catalysis; organocatalysis; visible-light-mediated reaction; N–O bond cleavage; acetyloxime esters; phenanthridines